The Use of Multimedia Technologies in Modern Teaching Methods - D.A.Mamaeva; D.D.Urazova (Zien Journals, 2022)
The article analyzes the scientific and theoretical foundations of the use of multimedia technologies in the modern educational process. The advantages of using multimedia technologies in the course process are also covered.
Keywords: Multimedia; multimedia tools; educational process; methodology